Key Performance Indicators Selection for PT. Len Railway System (LRS), Bandung, Indonesia - Binti Hassan, Radiah; Wibisono, Dermawan (The Indonesian Journal of Business Administration, 2016)
Abstract – Performance measurement for PT. Len Railway Systems (LRS) still not setup since it had been spin off from their main PT. Len Industri. The main objectives of this study are the following: i) to identify key performance indicators that affect the LRS performance; ii) to introduced a framework for key performance indicators (KPIs); and iii) to examine the weight and linkage of each KPIs to the organization performance. The results from questionnaire were used to develop a eight performance indicators. Then, there are categorized into three parts regarding IPMS framework; resource capability, internal process and organization results. Moreover, the eight indicators will be cascaded into the business and managerial level indicators for them to understand what are the activities to be done to achieve organization goals. Experts from their organization participated in the process of confirmation the weight of each indicators and linkage process. Next, analytical hierarchy process (AHP) had been used to reconfirm back the important and linkage of those KPIs selected to the organization objectives. Besides, the implementation plan is to start documented all the KPIs data from January until December 2016, then, there are two options for them at the end of year 2016; either to continue this proposed study by developing information technology system (ITS) for these KPIs in the future or review again the KPIs and framework proposed. Nevertheless, this study offered to other researchers for further discussion and research in other perspectives that can be cooperated together as one objective to improve company performance. Keywords: performance management system, key performance indicators